The economics of books - Marcel F. M. Canoy; Jan C. van Ours; Frederick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2005)
The tensions between books and book markets as expressions of culture and books as products in profit-making businesses are analysed and insights from the theory of industrial organisation are given. Governments intervene in the market for books through laws concerning prices of books, grants for authors and publishers, a lower value-added tax, public libraries and education in order to stimulate the diversity of books on offer, increase the density of retail outlets and to promote reading. An overview of the different ways by which countries differ in terms of market structures and government policies is given. Particular attention is paid to retail price maintenance. Due to differences between European countries it is not a good idea to harmonise European book policies. Our analysis suggests that the book market seems quite able to invent solutions to specific problems of the book trade and that, apart from promoting reading, there is little need for government intervention.
Keywords: Z11; D6; D4; L4; L1; 330; books; publishers; authors; diversity; monopolistic competition; retail price maintenance; subsidies; libraries; internet; Buch; Buchverlag; Monopolistischer Wettbewerb; Preisbindung; Internet